TRANSFORMASI DIGITAL IWA-QU DALAM MENDUKUNG KETERCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDG’s) PERSPEKTIF EKONOMI ISLAM - Rekha Afiah; Agustina Mutia; Eri Nofriza (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Sustainable Development Goals (SDG's) or what is known as environmentally friendly sustainable development created by the United Nations. An important role in achieving sustainable development goals or achieving sustainable goals can be at the forefront of achieving the SDG's economic pillars by creating jobs, providing decent working conditions, engaging in business innovation, and contributing to the economic, social and environmental impacts of business operations . In SDG's digital transformation, only two goals are used, namely goal 09 and goal 17, in Iwa-Qu's efforts to use digital marketing to maintain and create sustainable Iwa-qu products. This research aims to find out how digital transformation at Iwa-QU supports the achievement of sustainable development goals (SDG's) as well as digital marketing from an Islamic economic perspective. This research uses qualitative methods by checking the validity of the data using triangulation techniques. The results of the research show that digital transformation in achieving Sustainable Development Goals in Iwa-Qu businesses is seen from the aspect that there is still a lack of partnerships to reach global, and there are still obstacles to human resources.